Authenticity in Criminal Law, Criminalistics and Forensic Science - A. Y. Asnis; S. N. Khaziev (Теория и практика судебной экспертизы)
The authenticity of products, documents and some other objects is of paramount importance in all areas of human activity. Illicit manufacturing of the counterfeit goods, documents, money, and a number of other objects entails legal liability, including criminal.The questions about authenticity are commonly put before experts when appointing several forensic examinations: handwriting, traceological, commodity, materials, substances and products analysis. The techniques for forensic expert authenticity verification of a significant part of the objects require further improvement.The article reviews the objects, the forgery or falsification of which entails criminal liability, as well as the methods to establish the authenticity in criminalistics and forensic science. The authors also analyze the features of scientific substantiation of conclusions about authenticity in forensic examinations, and the questions of the evaluation of the expert opinions that resolved the issue in criminal cases. The article provides some examples of unique authenticity studies from the history of forensic science, as well as data on some contemporary studies of rare cultural objects. The authors highlight the need to further develop forensic methods that have become relevant concerning new objects known to contain deliberately false information.